Islamic Law Review of Scholarships Distributed Through Conventional Banks for FKIS Students at Trunojoyo University - Ishak (Penerbit Hellow Pustaka, 2025)
(Scholarship is a work program that exists in every school. The scholarship program The scholarship program is held to ease the burden on students in pursuing their studies, especially in terms of costs. The provision of scholarships to students is carried out selectively in accordance with the type of scholarship held, scholarship recipients excel in the scope of academic participants, the average value of the last report card, attendance attendance, behave well, have good morals, are active in organizations.The provision of scholarships is an income for those who receive and the purpose of the scholarship is to help ease the burden of tuition fees for students who get scholarships).